The perception of adolescents about old againg and the alderly being (Research, Society and Development, 2022)
This study aimed to understand the adolescents' perception of aging, old age and the elderly. It was an exploratory and descriptive qualitative research that was carried out in a Municipal Elementary School located in a municipality in the extreme south of Rio Grande do Sul - RS in 2018. The study participants were Elementary School students in the age group between 10 to 13 years. Data collection was carried out through individual interviews using an instrument containing open questions and occurred in March 2018. The data were analyzed using the thematic analysis technique. They showed that, in old age, the elderly can present deteriorating health, which are common chronic and degenerative diseases. They perceive Aging as a process in which there is maturation, accumulation of experiences and wisdom, associated with a greater availability of time to enjoy life and be active. However, there may also be a need for care and dependence, both physical and emotional. Old age is seen as the final phase of life and the elderly is projected with a stereotyped vision as an old person, with white hair and wrinkles on the body. It was concluded that investigating how these adolescents perceive these processes, may reflect discourses and behaviors passed on by different generations and, from that, favor means of education and research for health in different contexts of society.